LEGISLATIVE AND CURRICULAR HIGHLIGHTS FOCUSED UPON THE PHYSICAL DEVELOPMENT AND HEALTH AREA WITHIN THE EARLY EDUCATION FRAMEWORK, IN TERMS OF REGIONAL COORDINATES IN THE EUROPEAN UNION SPACE - Zsuzsa Szilárda GÁLL; Lorand BALINT (Cluj University Press, 2015)
In recent years, early education turned into a strategy for the European countries in their wish to support children's global development starting from birth up to reaching primary education. Two major courses of action are witness to this. The first course of action covers the legislative documents worked out on the occasion of events which benchmarked the policies related to children's early development, while the second one is given by the transposition of those legislated, namely into such curriculum documents, which are specific to the agreed age range. This study aims at a brief analysis of the curriculum in five countries, i.e. in Finland, Germany, Spain, Hungary and Romania, selected on grounds of the different regions criterion from within the European Union space. According to their respective levels, we tried to grasp the main - both common and specific - coordinates upon which the implementation of the early education, as a transitory form of the ante-preschool education towards the traditional instructive-educational process set for preschool education, relies. Also, in terms of national curriculum and/or guiding documents specific to the early education sector, we provide an overview of the significance enjoyed by the physical development and health area, in each such visited country. Repere legislative și curriculare centrate pe domeniul dezvoltării fizice și a sănătății în cadrul educației timpurii, raportate la coordonatele regionale din spațiul Uniunii Europene. In ultimii ani, educația timpurie a devenit o strategie a țărilor europene prin care se dorește sprijinirea dezvoltării globale a copilului, începând de la naștere până la trecerea în învățământul primar. Acest fapt, este reflectat prin două direcții majore de acționare. Prima direcție, cuprinde documentele legislative elaborate cu ocazia evenimentelor care au marcat politicile privind dezvoltarea timpurie a copiilor, iar cea de-a doua, este dată de transpunerea celor legiferate, în documentele curriculare specifice intervalului de vârstă convenit. Prezentul studiu, își propune o analiză succintă a curriculei din cinci țări, și anume: Finlanda, Germania, Spania, Ungaria și România, luând ca și criteriu de selecție a acestora, regiuni diferite ale spațiului Uniunii Europene. La nivelul lor, am încercat să surprindem principalele coordonate - comune și particulare - ce stau la baza implementării educației timpurii, ca formă tranzitorie de instruire antepreșcolară, către procesul instructiv - educativ tradițional, statuat la nivelul învățământului preșcolar. De asemenea, în cadrul curriculumului național și/sau a documentelor directoare specifice sectorului de educație timpurie, pentru fiecare țară vizată, am realizat o analiză a semnificației acordate domeniului dezvoltării fizice și sănătății.  Cuvinte cheie: educație timpurie, legislație, curriculă națională diferențiată, dezvoltare fizică și sănătate